(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2025)
The article presents a technology for shortcrust pastry products incorporating a composition of -walnut and sesame seed meals. Comprehensive research using organoleptic, physicochemical methods have proven the possibility and feasibility of using a composition of walnut meal and sesame seeds to improve the consumer properties and safety of shortbread cookies. In the developed shortcrust pastry products, the addition of meal led to an increase in proteins, fats, carbohydrates, namely fiber and minerals such as Calcium, Magnesium, Phosphorus, Iron. The composition of walnut meal and sesame meal was used in a ratio of 70:30, respectively. The developed mixture of meal was added to the recipe of the shortbread semi-finished product instead of flour in the amount of 20 %. The classic shortbread cookie recipe was used as the control sample. Shortbread cookies of the studied samples were baked at a temperature of 180-200°C for 10-12 min. The quality of shortbread cookies is assessed according to DSTU 3781:2014. A 5-point scale has been developedfor sensory evaluation of the quality of shortbread cookies. The possibility and expediency of using the composition of walnut meal and sesame meal to improve the nutritional properties and safety of shortbread cookies have been’ experimentally proven. After 25 days, such products retained the taste and aroma almost unchanged, due to slower oxidative processes resulting from the increased content of vitamin E. The peroxide value of the tested sample of cookies during this period was 16.6% less than the control sample, which also indicates slower oxidation of fats. Microbiological studies showed that after 25 days of storage, the total viable count (MAFAnM) in the cookies with the meal composition did not exceed established safety standards.